PMO-149 Tenofovir use in hepatitis B infection in pregnancy. (28th May 2012) - Chakrabarty, G; Clark, S; Forton, D
Abstract : Introduction: Antenatal screening and immunoprophylaxis reduces the perinatal transmission of hepatitis B virus but vertical infection may occur with high level viraemia. Antiviral therapy during the 3rd trimester of pregnancy may reduce the incidence of intrauterine infection. Lamivudine treatment reduces vertical transmission if given with immunoglobulin and vaccination in mothers with viral loads >10 8 IU/ml. There are no published trials for tenofovir in this context, although its use is supported by safety data from Antiretroviral Pregnancy Registryin USA (category B) with the added benefit of low viral resistance. Breastfeeding is not recommended as tenofovir is secreted in milk. Discontinuation of tenofovir after delivery carries the risk of hepatitis flares and liver decompensation. There are no guidelines for the use of antivirals in HBV-+ve pregnant women and treatment decisions are made on an individual basis. Methods: We initiated tenofovir 245 mg in five HBV monoinfected women in the 3rd trimester to prevent vertical transmission. Demographic, virological and outcome data were collected. Results: The patients were newly diagnosed during antenatal screening. They were all HBeAg+ve with high viral loads and normal ALT, presumed immunotolerant. All women wished to breastfeed and four were advised to stop tenofovir at delivery but one stopped 6 days before birth. 1 mother continued after delivery due to increased ALT during treatment with ultrasound evidence of liver disease. There were no reported adverse effects. During or at the end of treatment four patients had rises in ALT (>1–2ULN) but no jaundice or hepatic decompensation. All the babies were born healthy and received immunoglobulin and vaccination. Conclusion: This small series demonstrates the safety of tenofovir in the last trimester of pregnancy. Small increases in ALT were seen which could be due to pregnancy, the initiation or discontinuation of tenofovir. It is necessary to assess the stage of liver disease to guide the treatment strategy after birth, although this is not always feasible in pregnancy. The timing of tenofovir discontinuation is determined by breastfeeding. We recommended that breastfeeding should start 24 h after treatment cessation, although there is not an evidence base to support this. Long-term prospective studies are indicated to confirm efficacy, safety and to determine optimal discontinuation strategies in relation to breastfeeding. Competing interests: None declared.